Half metallic ferromagnetic and optical properties of ruthenium-doped zincblende ZnS: A first principles study. (January 2020) - Ghosal, Supriya; Luitel, Homnath; Mandal, Sujoy K.; Sanyal, Dirtha; Jana, Debnarayan
Abstract: Magnetic and optical properties of Ru-doped ZnS have been investigated using first principles calculations. Due to Ru dopants, nonmagnetic ZnS becomes magnetic. Ru induces half metallic ferromagnetism with a total magnetic moment of 2.0 μ B /supercell. Furthermore, the origin of ferromagnetism in Ru-doped ZnS can be explained by Ruderman-Kittel-Kasuya-Yosida (RKKY) like exchange interaction. Curie temperature analysis indicates the possibility of room temperature ferromagnetism from the structures. Moreover, reflectivity spectra in optical calculations successfully describe the metallic properties introduced in the doped system. Static dielectric constant for 6.25% Ru doping gives approximately six times higher value in long wavelength limit compared to the pristine. With a significant amount of Ru, the doped system becomes efficient for visible light absorption. The study reveals that Ru-doped ZnS can be a promising candidate for potential applications in spintronic and optoelectronic devices. Highlights: First principles calculations are employed to explore the effect of Ru doping in ZnS matrix. Half metallic ferromagnetic behaviour is introduced in the nonmagnetic structure due to Ru incorporation. RKKY interaction successfully explains the origin of ferromagnetism. Significant low energy peak in the reflectivity spectra confirms metallic properties.